2019
DOI: 10.2106/jbjs.18.00943
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory Prescription Limits and Opioid Utilization Following Orthopaedic Surgery

Abstract: Background: Since 2016, over half of the states in the United States have passed mandatory limits on opioid prescriptions, with limited evidence of effectiveness. In this study, we evaluated postoperative opioid prescriptions following orthopaedic surgery before and after the implementation of one of the earliest such laws. Methods: Following the implementation of state legislation limiting opioid prescriptions for opioid-naïve patients, 2 patient cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
66
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 12 publications
6
66
2
Order By: Relevance
“…A recent report by Reid et al. 20 demonstrated that the volume of opioids prescribed by orthopaedic surgeons decreased by approximately one-half after the implementation of statewide legislation restricting early postoperative opioid prescriptions in Rhode Island. Our state enacted legislation limiting postoperative opioid prescribing on January 1, 2018.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report by Reid et al. 20 demonstrated that the volume of opioids prescribed by orthopaedic surgeons decreased by approximately one-half after the implementation of statewide legislation restricting early postoperative opioid prescriptions in Rhode Island. Our state enacted legislation limiting postoperative opioid prescribing on January 1, 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Matzkin and colleagues 5 have corroborated this, with >80% of patients reporting satisfactory pain control after simple knee arthroscopy with NSAIDS alone. The use of preprocedure opiates also seems to play a large role in the usage of postoperative narcotics, [5][6][7][8] which underscores the importance of a comprehensive, educational, multimodal, and perhaps multidisciplinary approach to opioid-tolerant patients.…”
Section: See Related Article On Page 824mentioning
confidence: 99%
“…29 Recently, mandatory prescription limits have been associated with a reduction of opioid use after elective surgeries. [30][31][32][33] However, our knowledge of the potential strategies is limited, and none are currently broadly applied as standard of care interventions. The objective of our scoping review is to understand the strategies aiming at preventing chronic opioid use specific to adult trauma and acute care surgery patients.…”
Section: Open Accessmentioning
confidence: 99%